Analisis Pengukuran Kinerja Divisi It Menggunakan It Balanced Scorecard Pada Pt. Xyz - Edi Gunawan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research is to measure Information Technology performance in a company using IT Balanced Scorecard. Currently at PT. XYZ, there is no measurement of IT performance to know the contribution of IT department, so that the author plans to develop the IT Balanced Scorecard to measure the performance of IT department. IT Balanced Scorecard that has four perspectives is very well used to formulate IT Strategic targets that support the company’ strategic goals and measure IT performance. Plan to implement the IT Balanced Scorecard can be done by data collection, interview, and questionnaries, so we can know the initial conditions at IT department. With this analysis, can be seen directly the support of IT department to company strategic plan, get new standard for KPI (Key Performance Indicator) so in the future, performance improvement can be measured better and get seven strategic objectives used by the IT department.